Influence of nebulizer pressure drop on breathing profiles and aerosol deposition in human airways - Mišík, Ondrej; Prinz, František; Elcner, Jakub; Cabalka, Matouš; Bělka, Miloslav; Lízal, František (Elsevier, 2025)
Breathing flow rate profiles are crucial for predicting aerosol drug delivery. While aerosol particle characteristics are determined by the inhalation device, breathing profiles are patient-specific, making them an essential topic for personalized medicine. This study investigates the influence of nebulizer pressure drop on breathing profiles and subsequent aerosol deposition within human airways. Ten male subjects performed spontaneous, and slow and deep breathing manoeuvres through three different nebulizers (one jet and two mesh nebulizers). Breathing profiles were recorded, and the impact of nebulizer pressure drop on flow rate profiles was analyzed. Computational modelling of airway aerosol deposition was performed for particles ranging from 1 to 10 mu m in diameter, based on the recorded boundary conditions. The jet nebulizer exhibited the most significant flow rate decrease due to its high pressure drop, increasing particle deposition in the lower airways. These findings are important for personalized modelling and the application of a digital twin approach in treatment design, leading to more effective and targeted drug delivery.
Keywords: Nebulizer; Aerosol; Breathing profile; Inhalation; Airways; Deposition